2010
DOI: 10.1128/iai.01439-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of the (p)ppGpp Synthase RSH, a RelA/SpoT Homolog, in Stringent Response and Virulence ofStaphylococcus aureus

Abstract: In most bacteria, nutrient limitations provoke the stringent control through the rapid synthesis of the alarmones pppGpp and ppGpp. Little is known about the stringent control in the human pathogen Staphylococcus aureus, partly due to the essentiality of the major (p)ppGpp synthase/hydrolase enzyme RSH (RelA/SpoT homolog). Here, we show that mutants defective only in the synthase domain of RSH (rsh syn ) are not impaired in growth under nutrient-rich conditions. However, these mutants were more sensitive towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(213 citation statements)
references
References 58 publications
8
189
2
2
Order By: Relevance
“…However, loss of Rel did not lower persistence rates and, depending on the drug target, the ⌬rel strain, which has ϳ4-foldhigher basal levels of ppGpp due to constitutive alarmone synthesis by RelQ (54), produced a significantly higher number of persisters than the parent strain (45). This finding is a departure from the general concept that the SR mediates bacterial persistence, as activation of the SR in E. faecalis and Firmicutes in general is dependent on the Rel enzyme (43,45,66,74,(99)(100)(101). Resolution of this notion will require systematic studies on basal (p)ppGpp elevation in other related species.…”
Section: Figcontrasting
confidence: 55%
See 1 more Smart Citation
“…However, loss of Rel did not lower persistence rates and, depending on the drug target, the ⌬rel strain, which has ϳ4-foldhigher basal levels of ppGpp due to constitutive alarmone synthesis by RelQ (54), produced a significantly higher number of persisters than the parent strain (45). This finding is a departure from the general concept that the SR mediates bacterial persistence, as activation of the SR in E. faecalis and Firmicutes in general is dependent on the Rel enzyme (43,45,66,74,(99)(100)(101). Resolution of this notion will require systematic studies on basal (p)ppGpp elevation in other related species.…”
Section: Figcontrasting
confidence: 55%
“…Specifically, reduction in cellular pools of the coeffector GTP by (p)ppGpp results in less stable CodY-DNA interactions, thereby alleviating CodY regulation (71). Importantly, the (p)ppGpp/CodY association is critical for nutrient stress tolerance and virulence in several bacterial pathogens (72)(73)(74)(75)(76)(77)). Yet, the relative contributions of GTP-and CodY-dependent mechanisms for stress tolerance and virulence controlled by (p)ppGpp are not entirely clear, as GTP depletion can also affect stress survival in a CodY-independent manner (67,68).…”
Section: (P)ppgpp and Codymentioning
confidence: 99%
“…Mutations in sarA decrease S. aureus biofilm and increase antibiotic susceptibility both in vitro and in vivo (31,57), whereas mutations in mecA, which encodes penicillin binding protein 2a, impede resistance to ␤-lactam antibiotics (58). Several other genes identified in our screen have also been associated with biofilm formation (codY), ␤-lactam resistance (fmtC and vraR), or both processes (rsbU, rsbW, fmtA, and rsh) (4,10,16,(33)(34)(35)(36)(37)(38)(39). In addition, two genes (ilvE and fmtA) were previously shown to be induced by cell wall stress (36), and four genes (sarA, atl, codY, and rsbU) were specifically shown to limit biofilm in strain USA300 (38).…”
Section: Discussionmentioning
confidence: 99%
“…6C). Several of these genes have previously been shown to play a role in S. aureus ␤-lactam resistance (fmtA, fmtC, rsh, and vraR), biofilm formation (codY, rsbU, and rsbW), or both processes (atl, mecA, and sarA) (4,10,16,(33)(34)(35)(36)(37)(38)(39). Two genes (ilvE and fmtA) were previously shown to be induced by cell wall stress (36), and one gene (atl) was previously shown to be required for induction of biofilm by sub-MIC methicillin in strain LAC (16).…”
Section: Resultsmentioning
confidence: 99%
“…The genome of S. aureus also encodes two other monofunctional synthetases, RelP and RelQ, and transcription of these genes increases when cells are exposed to cell wall-targeting antimicrobials (20,21). Recent work on S. aureus has shown that the ability to switch on the stringent response is essential for its virulence and is required for the organism to cause chronic infections (22)(23)(24)(25).…”
mentioning
confidence: 99%